Nellore cows and their calves during the lactation period: performance, intake, milk composition, and total apparent digestibility - Silva, Luiz Fernando Costa e; Engle, Terry Eugene; Valadares Filho, Sebastião de; Rotta, Polyana Pizzi; Villadiego, Faider Alberto Castaño; Silva, Flávia Adriane Sales; Martins, Edilane Costa; Silva, Luis Henrique Rodrigues; Paulino, Mário Fonseca (Tropical Animal Health and Production, 2015)
An experiment was conducted to evaluate intake and nutrient digestibility, performance, milk composition, and microbial efficiency of Nellore cows and their calves during lactation. Fifteen Nellore cows were fed corn silage and concentrate (85:15). After calving, calves were kept with their dams for 2 months then separated and housed in individual pens adjacent to their dams. Cows were milked every 15 days over 7 months to estimate milk intake of the calves. During lactation, nutrient intake decreased (P < 0.01) for cows, while nutrient digestibility increased (P < 0.001). Starting 2 months post-calving, calves were offered concentrate (5 g/kg body weight (BW)) and roughage. An increase in DM digestibility was observed for calves in the third month of age, probably due to an associative effect between milk, concentrate, and roughage, which increased DM digestibility without increasing DM intake. Average daily gain (ADG) of the calves increased (P < 0.001) during lactation period. Microbial efficiency (g mCP/kg total digestible nutrients (TDN)) did not change (P > 0.05) in either cows or their calves during lactation period. However, nutrient digestibility decreased for calves during this period. Nellore cows produced milk with average of 4.58 % lactose, 5.61 % fat, and with milk protein increasing from 3.6 to 4.0 % as lactation progressed.
Keywords: Beef cattle; Bos indicus; Lactation; Milk composition; Weight gain